(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Quetiapine is an atypical antipsychotic used for the treatment of schizophrenia, bipolar disorder, and major depressive disorder. Use of quetiapine has been associated with serum aminotransferase elevations and in rare instances with clinically apparent acute liver injury. The structure and the ground state energy of the molecules under investigation has been analyzed employing DFT B3LYP level. The optimized geometry and their properties such as equilibrium energy, frontier orbital energy, dipole moment and vibrational frequencies have been used to understand the activity ofQuetiapine. The calculated highest occupied molecule orbital or HOMO and the lowest un-occupied molecular orbital or LUMO energies shows that charge transfer within the molecule. The vibrational spectra of IR and Raman have been interpreted with the help of B3LYP level of theory with the 6-31G basis set from the Density function theory.